Promoting a School Companion Competency Model to Address New Education Policies and the Challenges of the Digital Era - Yayah Rahyasih; Johar Permana; Liah Siti Syarifah (Pedagogi: Jurnal Ilmu Pendidikan, 2026)
This study aims to conceptualize and describe a new school companion competency model designed to guide educational practitioners in Indonesia, following a recent policy reform that abolished the official role of school supervisors. This reform coincides with the accelerating digital transformation of education, demanding new professional capacities that emphasize collaboration, adaptability, and digital fluency. To address this gap, the study employed a mixed-methods design over a nine-month period, combining in-depth semi-structured interviews and focus group discussions with purposively selected participants who had direct experience in supervisory role transitions. The findings identified the Instructional Coaching Competencies (ICC) framework as the most relevant model for current educational needs. The ICC model represents an adaptive, integrative, and holistic approach consisting of three interrelated dimensions: Digital Instructional Leadership, Digital Ethics and Communication, and Transformational Coaching. Collectively, these dimensions redefine supervision as an act of facilitation and reflective partnership rather than bureaucratic inspection. The results hold substantial relevance beyond Indonesia, particularly for countries with decentralized education systems undergoing similar policy transitions. The model also provides practical guidance for school principals in strengthening leadership and professional competence in the digital era. With strong confidence, this study recommends the broader application of the ICC framework and encourages future research using a quasi-experimental approach to validate its reliability and impact on teaching performance and instructional quality.